Densidade Populacional e Ecologia de um grupo macaco-prego-de-crista (Cebus robustus; Kuhl, 1820) na Reserva Natural Vale - Waldney Pereira Martins (2010)
Cebus robustus is a species of capuchin monkey being considered in the Brazilian list of endangered species as vulnerable and categorized as endangered by the IUCN. Its geographic distribution is limited in the South by the rivers Doce and Suaçui Grande and in the north through the river Jequitinhonha in the states of Bahia, Espitito Santo and Minas Gerais. So far there has not been any study on the ecology of this species. There are no recent estimates on population sizes so that new estimates are a necessary base for the development of action plans oriented to the conservation of this species. The objective of this study was to estimate the population density of Cebus robustus in the Reserva Natural Vale and to study the activity patterns and home range behavior of one group. The line transect method was used to estimate the population density, recording 75 sightings along 314.7 km walked within 9 months. Both analysis revealed a lower C. robustus densities (0.54 groups/km²) if compared to former studies that were conducted 13 years ago. However this could be due to difference between sampled efforts but a population decline. To study the ecology of C. robustus one group of 15 individuals was monitored during 10 months between March 2009 and February 2010 totaling 370 hours of observations. The group inhabited a forest with nearby native and exotic plantations. The behavioral patterns were analyzed separately for a dry and rainy season and there was no significant difference in the behavioral patterns between the two seasons, except for resting behavior that was more dominant during the rainy season. The phenology study of the reforested area revealed the production and continuous provision of fruits for C. robustus during the whole year. Even during the season with fruits available in the native forest the group consumed a considerably amount of exotic fruits from the plantation. This leads to the assumption that in this area exotic fruits represent a major item in the diet of C. robustus and that they substitute native fruits in the forest. The results show a pronounced environmental plasticity and adaptation potential of C. robustus. In order to increase the knowledge about the ecological performance of this species in more natural habitats further studies on this species should be conducted in less anthropized areas. During the period of this study the group used a home range of 110.5 ha that represents the smallest home range sizes that have been recorded so far within the genus Cebus. As the study group inhabited a forest closed to exotic fruit plantations its relatively small home range may be due to the considerable nutricional support given in this patch and making it unnecessary to forage over wider areas. This study presents the first ecological data for C. robustus but more studies with other groups and in others areas could conducted to be integrated in management plans for its conservation